2018
DOI: 10.1111/emr.12292
|View full text |Cite
|
Sign up to set email alerts
|

Nest box design for a changing climate: The value of improved insulation

Abstract: Summary Mean air temperatures and the frequency, intensity and duration of extreme weather events such as heatwaves are increasing due to climate change. Nest boxes experience more variable and extreme temperatures than natural cavities, which may reduce survival and reproductive success of the species which utilize them, but little is known about the factors which drive nest box temperature profiles. We quantified the potential for retrofitted insulation on nest boxes to modify internal temperatures and to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The dangers to bats from climate change are manifold; in addition to heat stress, changes in phenology, physiology, and distribution can be expected (Jones & Rebelo, 2013). With 2019 being the second warmest year on record (mean global temperature anomaly of +0.95°C above average; NOAA, 2020), temperatures expected to increase 0.4–2.6°C by mid‐century (IPCC, 2014), and heat waves expected to increase in frequency, intensity, and duration (Meehl & Tebaldi, 2004), overheating events in bat boxes may become more common (Bideguren et al, 2018; Larson, Eastwood, Buchanan, Bennett, & Berg, 2018). Currently, we lack empirical research on the impacts of climate change on bat box designs and deployment strategies (but see Bideguren et al, 2018; Larson et al, 2018).…”
Section: Increasing Popularity Uncertainty and Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The dangers to bats from climate change are manifold; in addition to heat stress, changes in phenology, physiology, and distribution can be expected (Jones & Rebelo, 2013). With 2019 being the second warmest year on record (mean global temperature anomaly of +0.95°C above average; NOAA, 2020), temperatures expected to increase 0.4–2.6°C by mid‐century (IPCC, 2014), and heat waves expected to increase in frequency, intensity, and duration (Meehl & Tebaldi, 2004), overheating events in bat boxes may become more common (Bideguren et al, 2018; Larson, Eastwood, Buchanan, Bennett, & Berg, 2018). Currently, we lack empirical research on the impacts of climate change on bat box designs and deployment strategies (but see Bideguren et al, 2018; Larson et al, 2018).…”
Section: Increasing Popularity Uncertainty and Riskmentioning
confidence: 99%
“…For example, Doty, Stawski, Currie, and Geiser (2016) found maximum temperatures in white, single‐chamber bat boxes were 7.5°C cooler than in black bat boxes; notably, however, bats preferentially selected black bat boxes in their wintertime study, likely due to the thermal benefits of a warmer microclimate (Wilcox & Willis, 2016). Using dense construction materials with low thermal conductance could also reduce overheating risk (Bideguren et al, 2018) and lead to more stable microclimates (Larson et al, 2018). For example, black, four‐chambered bat boxes made of wood‐cement (a molded mixture of wood shavings and cement) buffered high temperatures better than an identical design made out of plywood; the wood‐cement design was up to 3.2°C cooler during the summer (Rueegger, 2019).…”
Section: Mitigating the Riskmentioning
confidence: 99%
“…These findings were in stark contrast to the expectations of greater heat retention in tree cavities that insulate most efficiently. Such expectations were based on observations from nest boxes, where those with improved insulation resulted in a greater internal temperature increase in response to an artificial heat source within, compared to those nest boxes without additional insulation (Kearney et al 2011;Larson et al 2018). Following installation of heat pads, Grüebler et al (2014) recorded only a slightly greater temperature increase in empty tree cavities compared to nest boxes, which insulated less effectively.…”
Section: Modification Of Cavity Microclimate In Relation To Cavity Inmentioning
confidence: 99%
“…Moreover, the amount of heat generated by endothermic animals and retained inside cavities might differ between sites, with presumably greater amount of heat retained in those that insulate more efficiently, i.e. more effectively reduce heat loss from inside (Kearney et al 2011;Larson et al 2018). Thus, the microclimate of occupied cavities might depend on a combination of ambient temperature, cavity insulation and the heating activity of endothermic occupants.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated that: white boxes, box materials that buffer warm ambient temperature (e.g., wood-cement over plywood) and box designs that comprise a temperature gradient within the box (e.g., multiple chambers with vents) can negate hot ambient temperature to some extent. Consideration of these box design elements and identifying other design elements to further improve the buffering capacity from extreme heat [56,67] may be particularly important given the predicted climate warming and increased periods of extreme heat [68].…”
Section: Thermal Limits and Box Temperaturementioning
confidence: 99%